Economy-wide CO 2 Emission Reduction Due to Carbon Tax in the Power Sector: A Structural Decomposition Analysis - Marpaung, Charles O.P.; Shresta, Ram M. (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
In  this  paper,  a  structural  decomposition  analysis based  on  an  input-output  framework  has  been  developed  to examine the factors, which affect the economy-wide CO 2  emission changes due to the introduction of carbon tax in the Indonesian power sector during 2011-2030. There are three major components that affect the total economy-wide change in CO 2  emissions, i.e., fuel mix-, structural-, and final demand- effects. The results show that, the CO 2  mitigation under the carbon tax of US$200/tC would be 20.5 times higher than that with the carbon tax rate of US$5/tC.  The fuel mix effect is found to be most influential in reducing the CO 2  emission during the planning horizon under all of the carbon tax  rates  considered  and  is  followed  by  the  final  demand-  and structural-effects.